My son wouldn't look at me in the eyes an interpretative phenomenological analysis on fathers' experiences of children with autism. - Cajano, Hasmin S.; Olaya, Mary Rose G.; Rotap, Shirly V. (Hasmin S. Cajano, 2013)
What are the father's experiences of living with a child with autism, and what do these experiences mean? This study revolves around the fathers' experiences with their children diagnosed with autism. Data for this study was generated through a semi-structured interview schedule with fathers who are considered to be the primary caregivers of children with autism. Specifically, this study employs Interpretative Phenomenological Analysis which aims to "explore in detail how participants are making sense of their personal and social world". Hence, the father's meaning-making of his experiences is interpreted by the researchers to provide a holistic grasp of the process. With this, six themes have emerged from the analysis: 1) the expected child 2) confusion 3) feeling of loss 4) coping strategies 5) resignation to acceptance and; 6) learning and insights. Participants were able to form the belief that their children who have autism are their purpose as well as the reason why they still continue to live and to be stronger in facing life's challenges. Thus, it would seem that the meaning of their lives is derived from their children with autism. Further studies should be conducted that would utilize more respondents to be able to comprehend the diversity of the experiences of different fathers with different life approaches so that further comparisons can be made and to be able to formulate other important themes within the meaning-making of the participants.